Help the Spanish child refugees! (leaflet)
ever, are still unable to return to Spain, because their parents are refugees themselves, or prisoners of war, or dead or missing. Ultimately, these children, too will go back, but until we can restore them to their parents or next of kin, they are entirely dependent upon us for food, shelter and a chance to build up their lives again. The Basque Children's Committee is responsible for some forty homes all over England, Wales and Scotland. These have been maintained from the start by the generosity of the British public. Help has come from all sections of the community — the Churches, local government bodies, voluntary organisations of every kind (including Boy Scouts and Girl Guides), school-children, and thouands of individual sympathisers. The need for more funds, however, has now become urgent. The children will probably not be with us very much longer, but money is needed to keep them in this country until their parents and relatives are able to receive them. Safe In England, a Spanish Refugee Boy goes on with his schooling. According to an old Basque Custom, Refugee Children from Bray Court, Maidenhead, put out their shoes for presents on the Feast of the Kings (Twelfth Night). 292/946/18a/45(iii)